ChemInform Abstract: Fe‐Catalyzed Regioselective Friedel—Crafts Hydroxyalkylation of N‐Substituted Glyoxylamide with Indoles. Issue 22 (12th May 2016) - Zheng, Yang; Li, Ren‐Jun; Zhan, Zhen; Zhou, Yan; Hai, Li; Wu, Yong
Abstract: Efficient and highly regioselective, Fe‐catalyzed Friedel—Crafts hydroxyalkylation reactions of various indoles using N‐substituted glyoxylamides are described.